2020
DOI: 10.14309/ctg.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Application of Behavioral Economics Principles Improves Participation in Mailed Outreach for Colorectal Cancer Screening

Abstract: INTRODUCTION: Colorectal cancer (CRC) is a major cause of cancer-related morbidity and mortality in the United States. Although various interventions have improved screening rates, they often require abundant resources and can be difficult to implement. Social psychology and behavioral economics principles offer an opportunity for low-cost and easy-to-implement strategies but are less common in clinical settings. METHODS: We randomized 2,000 patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…However, competing demands on attention, behavioral inertia, and unwieldy processes that make it hard to follow through on intentions likely conspire to make a single, timely, targeted reminder helpful. [2][3][4][5] The emails' behavioral features-active choice, appeal to authority, and emphases on scarcity, social norms, and risk recalibration (eAppendix in Supplement 1)-may have contributed to their effect. The 3.17% absolute increase in vaccination appointments we observed is larger than many real-world nudges 6 and may be greater among recipients who are less hesitant about receiving the vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, competing demands on attention, behavioral inertia, and unwieldy processes that make it hard to follow through on intentions likely conspire to make a single, timely, targeted reminder helpful. [2][3][4][5] The emails' behavioral features-active choice, appeal to authority, and emphases on scarcity, social norms, and risk recalibration (eAppendix in Supplement 1)-may have contributed to their effect. The 3.17% absolute increase in vaccination appointments we observed is larger than many real-world nudges 6 and may be greater among recipients who are less hesitant about receiving the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to determine whether individually addressed emails designed with behaviorally informed features [1][2][3][4][5] could increase vaccination registration compared with a delayed control group.…”
Section: Introductionmentioning
confidence: 99%
“…The message builds in previous research which suggests that perceived scarcity may enhance the value of the medical service ( BROCK, 1968 ). Experiments have shown that people perceive products which are scarce because of limited availability as costlier and more appealing as products that are abundantly available ( Verhallen, 1982 , Verhallen and Robben, 1994 ) A recent US study found that a behavioral intervention, which also featured implied scarcity, increased CRC screening ( Bakr et al, 2020 ). Similar to our study, they implied scarcity by the unique opportunity of receiving a FIT kit (“you have been selected”).…”
Section: Methodsmentioning
confidence: 99%
“…While these interventions are effective at improving overall uptake, they have only partially been adopted, due to a lack of evidence supporting their cost-effectiveness (for example, telephone reminders are not recommended by the European Union Committee for Quality Assurance in Bowel Cancer Screening, as they are not considered cost-effective) ( von Karsa et al, 2013 ). As such, there is growing interest in the search for new low-cost interventions, such as those which involve enhancing existing invitation materials through the use of insights from behavioral economics ( von Karsa et al, 2013 , Purnell et al, 2015 , Barnes et al, 2016 , Schwartz et al, 2017 , Stoffel et al, 2019 , Bakr et al, 2020 , Huf et al, 2020 , Stoffel et al, 2021 ) These approaches build on the concept that the screening decision is influenced by the way in which the choice is presented, and are potentially cost-neutral, as they only involve manipulating the presentation and content of the invitation materials ( Purnell et al, 2015 , Schwartz et al, 2017 , Stoffel et al, 2019 , Bakr et al, 2020 , Huf et al, 2020 , Stoffel et al, 2021 , Mehta et al, 2017 , Mehta et al, 2018 , Stoffel et al, 2019 , Stoffel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation